ANALISIS YURIDIS SELEKSI PIMPINAN KOMISI PEMBERANTASAN KORUPSI BERDASARKAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 30 TAHUN 2002 TENTANG KOMISI PEMBERANTASAN TINDAK PIDANA KORUPSI - Syahputra, Adi; Firdaus, Emilda; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Law No. 30 of 2002 on the Corruption Eradication Commission did not provide adequate space for people to participate in the selection of members of the Corruption Eradication Commission. This is due to the participation of ancillary instruments are not designed to accommodate the substantive public participation. One of them is the lack of regulation of openness at both the government and the elections in the House of Representatives. Therefore, strengthening the participation ancillary instruments necessary to ensure the selection of the leadership of such an independent agency of the Corruption Eradication Commission is not co-opted by a particular domain authority. The key to traveling Eradicate Corruption Commission certainly fill the human resources of this organization. Selection Commissioner Eradicate Corruption Commission selection process is one of the heads of state institutions that attract the most attention. A variety of interests can not be separated from the actions of the Corruption Eradication Commission to perform a variety of work to eradicate corruption, especially in sectors prosecution. Then no other way that can be done to keep the Corruption Eradication Commission in addition to ensuring a selection on objective, transparent and without conflicts of interest (conflict of interest). The key to the process is the selection of a selection committee that is credible as a filter candidates.Even in reality during this time, pansel contribute to determine the character of the Corruption Eradication Commission for four years. The existence of the House of Representatives to be part of the checks and balances often does not work. This is due to the House of Representatives often using political reasoning in the selection of public officials. In order to get the best commissioner, it's time for the selection of the Corruption Eradication Commission in the redesign of the terms concerning the selection of candidates and the mechanisms associated with the map Eradicate Corruption Commission needs of the organization.Additionally you need further adjustment in the form of a specific regulation that public participation in the selection process is not only meets the formal requirements. In terms of public administration, the selection process Eradicate Corruption Commission Leaders in the House of Representatives is the implementation of the right